Potensi Daun Kastuba (Euphorbia Pulcherrima) Sebagai Antimalaria Plasmodium Falciparum - ELVINA VERONICA; NI KADEK SINTA DWI CHRISMAYANTI (HANG TUAH MEDICAL JOURNAL, 2020)
Abstract Introduction: Around 41% of people in the world at risk of malaria due to plasmodium infection. Plasmodium falciparum is the most dangerous malaria infection compared to another plasmodium because it causes 90% of total malarial deaths. ACT (Artemisinin Combination Therapy) is the gold standard of malaria medicine, is starting to become resistant, so other alternatives are needed. Poinsettia plants (Euphorbia pulcherrima) are ornamental plants and contain compounds that potential as anti-parasites. Objective: To aims the potential of poinsettia leaves as an antimalarial alternative to Plasmodium falciparum in malaria treatment. Methods: Literature studies using in vivo, in vitro, in silico research articles, and literature reviews from national and international journals accessed from Google Scholar, Elsevier, Science Direct, and Pubmed in the last 10 years using malaria, antioxidants, anti-malaria, Plasmodium falciparum, and Euphorbia pulcherrima as keywords. There were 22 relevant articles used in this literature review. Results: Antioxidants in poinsettia leaves inhibited plasmodium growth by inhibit nutrient transport at new permeation pathways and prevent hemozoin ban. Terpenoids in poinsettia inhibit schizont and trophozoite in an earlier asexual phase of Plasmodium falciparum by inhibiting isoprenoid biosynthesis. Conclusion: Poinsettia (Euphorbia pulcherrima) has the potency to be an antimalarial alternative against Plasmodium falciparum. Need further research about the dosage and side effects of the usage